Diseño y simulación computacional de una estructura interna para protector de espalda para motociclistas (2023)
Among motorized means of transport, motorcycles are more vulnerable to impacts, which significantly increases the risk of accidents, and therefore the physical injuries caused to people and the severity of these injuries. To prevent these injuries and/or reduce their severity, motorcycle protectors are available in the market whose design is fairly standardized in terms of materials, since two types of materials are usually used for their development: soft materials such as foam (usually D3O or EVA (Ethyl Vinyl Acetate) or rigid materials such as polypropylene. In the case of foam protectors, these have limitations when protecting against impacts, since they are flexible and transmit more energy than recommended to avoid injuries (Standard EN 1621-2), and this flexibility does not prevent deformations in the spine of the person. On the other hand, rigid protectors, which prevent torsion of the back, are usually more expensive than foam protectors. For example, it is observed that within the "Alpinestars" brand, a rigid protector can have a cost of approximately $120 USD while a foam protector of the same brand can have a much lower value, of approximately 60 USD, which also turns out to be a high price for an average person in the country, since at the time of the study this price turns out to be around $260000 COP. The objective of this project is the design and computational simulation of an internal structure of a back protector for motorcyclists, whose development, analysis and evaluation of results, serve to obtain information to improve the protection elements for motorcyclists, by mitigating or eliminating the weak points of protectors that are marketed in the future, and/or support future research related to the design of protectors. In this study, geometries and materials previously used in other applications related to impact protection are used, mainly in the automotive industry, since in this sector, protective elements that seek to disperse the energy of impacts caused by accidents on vehicle occupants are developed, and these elements prove to be quite effective in reducing physical injuries to people and their temporary or permanent consequences. According to the results obtained from the design and simulation developed in this study, it was possible to establish that carbon fiber and HDPE in oval geometry protectors serve to improve the protection elements for motorcyclists, since these materials are capable of complying with the levels of force transmitted to the body established by the EN 1621-2 Standard (of the order of 20 kN), attenuating even a little more than the force established by the standard, transmitting around 15kN.